Does Disagreement Facilitate Informed Trading? - Cookson, J. Anthony; Fos, Vyacheslav; Niessner, Marina (Journal of Financial and Quantitative Analysis, 2026)
Abstract Using high-frequency disagreement data from the investor social network StockTwits, we find that greater unsophisticated disagreement facilitates informed buying and selling. During periods of overvaluation, the facilitating effect of disagreement on trading is dampened for informed buyers but is amplified for informed sellers. These findings are unexplained by sentiment, news, and retail order flow, and they remain when we measure disagreement overnight and disagreement of technical investors, which alleviates the concern that disagreement and informed trading respond to a common shock. These findings suggest that informed traders respond meaningfully but differently to valuation changes induced by unsophisticated disagreement.